Prevalence of Cognitive Impairment and its Correlates among Rural Elderly Population in a Tribal Region of Eastern Maharashtra, India - Umakant G. Shidam; Rupesh A. Gedam; Arghya Das (Preventive Medicine: Research & Reviews, 2025)
Objective: To determine the prevalence and explore the correlates of cognitive impairment in the elderly. Materials and Methods: A community-based cross-sectional study was carried out among 184 elderly aged 60 years and older in a rural area of eastern Maharashtra, India. Data were collected during household visits using a pre-designed pre-tested questionnaire. All eligible elderly were screened for cognitive impairment using the Mini-Mental State Examination (MMSE). Results: Of the 184 participants, 44.5% had cognitive impairment. In the logistic regression model, being female [aOR: 4.08 (95% CI: 1.81-9.22)], having less than 8 years of schooling in older age [aOR: 8.31 (95% CI: 2.21-31.21)], and living in poverty [aOR: 2.77 (95% CI: 1.07-7.19)] were identified as significant factors that increase the likelihood of cognitive impairment. Conclusion: The current research reveals a notable prevalence of cognitive impairment. It is essential to prioritise care for the vulnerable population by enhancing services, particularly in resource-limited settings, such as rural areas.